Proactive and responsive export market orientation behaviours, antecedents, and firm performance: A qualitative study on exporting SME's - Abdul-Talib, Asmat-Nizam; Abd Razak, Ili Salsabila (IGI Global, 2020)
This paper details about the qualitative study of proactive and responsive export market orientation. An interview series was conducted to assess whether the issue of proactive and responsive export market orientation exist among exporters, identification of the exporters' characteristics (antecedents) and understand the behaviors effect on performance consequences. Findings from the interview were recorded in a qualitative codebook. Discussions and conclusion made on the qualitative findings revealed that the issue of proactive and responsive export market orientation is present, different characteristics lead to different behaviors, and the behaviors affect the exporters' performance consequences differently.